2021
DOI: 10.1038/s41598-021-84312-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the cotton CLE polypeptide signaling gene family in plant growth and development

Abstract: The CLAVATA3 (CLV3)/EMBRYO SURROUNDING REGION (ESR)–RELATED (CLE) gene family encodes a large number of polypeptide signaling molecules involved in the regulation of shoot apical meristem division and root and vascular bundle development in a variety of plants. CLE family genes encode important short peptide hormones; however, the functions of these signaling polypeptides in cotton remain largely unknown. In the current work, we studied the effects of the CLE family genes on growth and development in cotton. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“… (Guo et al 2022 ; Liu et al 2021 ; Uzair et al 2021 ; Xu et al 2017b ) Conserved ( Arabidopsis , rice, etc.) CLEs Nucleus, plasma membrane CLV1, CLV2, CRN, RPK2 Shoot apical meristem size regulation, pollen tube growth, stress response (Clark et al 1995 ; Takahashi et al 2019 ; Wan et al 2021 ; Zhang et al 2021 ) Conserved ( Arabidopsis , rice, etc.) GASAs Extracellular Plant growth and development, response to phytohormones, abiotic stresses, defense against pathogen (Almasia et al 2008 ; Conlan et al 2011 ; Ko et al 2007 ; Muhammad et al 2019 ; Pan et al 2019 ; Sun et al 2013 ; Wang et al 2009b ) -: Not identified …”
Section: Discussionmentioning
confidence: 99%
“… (Guo et al 2022 ; Liu et al 2021 ; Uzair et al 2021 ; Xu et al 2017b ) Conserved ( Arabidopsis , rice, etc.) CLEs Nucleus, plasma membrane CLV1, CLV2, CRN, RPK2 Shoot apical meristem size regulation, pollen tube growth, stress response (Clark et al 1995 ; Takahashi et al 2019 ; Wan et al 2021 ; Zhang et al 2021 ) Conserved ( Arabidopsis , rice, etc.) GASAs Extracellular Plant growth and development, response to phytohormones, abiotic stresses, defense against pathogen (Almasia et al 2008 ; Conlan et al 2011 ; Ko et al 2007 ; Muhammad et al 2019 ; Pan et al 2019 ; Sun et al 2013 ; Wang et al 2009b ) -: Not identified …”
Section: Discussionmentioning
confidence: 99%
“…For example, when weather cold-induced changes in non-coding gene expression had a significant effect on the cold tolerance of cotton seedlings, TRV2-CLA1 was used as a positive control to determine that silencing of lincRNA XH123 resulted in increased sensitivity to cold injury [41]. When studying the function of the CLE gene family in cotton, CLA was again used as a positive control, and it was found that the silencing of GhCLE5 in cotton resulted in dwarf seedlings [42]. Inhibition of GauGRAS1 by VIGS resulted in glandless stems and petioles of Gossypium australe compared with positive control TRV-CLA and negative control TRV empty vector [43].…”
Section: Discussionmentioning
confidence: 99%
“…The 12-peptide characteristic sequences of different subfamilies of CLE proteins are various, but the amino acids at some sites are still very conservative . At present, CLE gene families of many species have been identified and 26, 15, 93, 104, 116, 84 and 44 CLE genes were identified in cucumber, tomato, cotton, wheat, Brassica napus, soybean and common bean (Qin et al 2021;Zhang et al 2014;Wan et al 2021;Li et al 2019;Han et al 2020;Hastwell, Gresshoff, and Ferguson 2015). The number of CLE genes varies greatly among different species, indicating that CLE genes have undergone different evolutionary choices.…”
Section: Introductionmentioning
confidence: 99%